PENGARUH MASASE ABDOMINAL EFFLEURAGE DAN KOMPRES AIR HANGAT TERHADAP NYERI DISMINORE PADA MAHASISWI KEBIDANAN STIKES AS SYIFA KISARAN TAHUN 2024: PENGARUH MASASE ABDOMINAL EFFLEURAGE DAN KOMPRES AIR HANGAT TERHADAP NYERI DISMINORE PADA MAHASISWI KEBIDANAN STIKES AS SYIFA KISARAN TAHUN 2024 - Juliana; Jahriani, Nani; Tambunan, Lili Yuliana (Maternity and Neonatal : Jurnal Kebidanan, 2024)
Background: Based on 2020 World Health Organization (WHO) data, the incidence of dysmenorrhoea is 1,769,425 (90%) women suffering from dysmenorrhoea, with 10-16% suffering from severe dysmenorrhoea. The incidence of dysmenorrhea in the world is very high. Symptoms of primary dysmenorrhea usually appear in women of childbearing age and women who have never been pregnant (Indah & Susilowati, 2022). Astarto wrote that dysmenorrhea is a type of menstrual discomfort that mostly attacks the lower abdomen, but can also spread to the upper thighs, calves, lower back and waist. There are two types of dysmenorrhea: primary dysmenorrhea, and secondary dysmenorrhea. Research Objective: To determine the effectiveness of abdominal effleurage massage and warm water compresses on dysmenorrhea pain in female midwifery students at STIKes As Syifa Kisaran in 2024. Method: The research method used is a type of quantitative research, namely quasi-experimental design with a one-group pre test-post design. test design. Research Results: Based on the analysis of research data, it was found that the effect of abdominal effleurage massage and warm water compresses on dysmenorrhea pain in midwifery students was very effective in reducing dysmenorrhea pain in midwifery students, where the results of the study showed the intensity of dysmenorrhea pain in midwifery students before and after it was carried out. abdominal effleurage massage and warm water compresses with a mean value of 1.96. This means that the dysmenorrhea pain scale in midwifery students after abdominal effleurage massage and warm water compresses experienced a decrease in dysmenorrhea pain. Keywords: Abdominal effleurage massage and warm water compress, dysmenorrhea pain